Suberoylanilide hydroxamic acid – a potential epigenetic therapeutic agent for lung fibrosis? - Wang, Z.; Chen, C.; Finger, S.; Kwajah, M.; Jung, M.; Schwarz, H.; Swanson, N.; Lareu, Ricardo; Raghunath, M. (European Respiratory Society, 2009)
Pulmonary fibrosis represents a fatal stage of interstitial lung diseases of known and idiopathic aetiology. No effective therapy is currently available. Based on an indication-discovery approach we present novel in vitro evidence that the histone deacetylases inhibitor suberoylanilide hydroxamic acid (SAHA), an FDA approved anti-cancer drug, has antifibrotic and anti-inflammatory potential. Human lung fibroblasts (fetal, adult and idiopathic adult pulmonary fibrosis) were treated with transforming growth factor (TGF)-β1 with or without SAHA. Collagen deposition, α-smooth muscle actin (α-SMA) expression, matrix metalloproteinase (MMP)1 activity, tissue inhibitor of MMP (TIMP)1 production, apoptosis and cell proliferation were assessed. Pro-inflammatory cytokines relevant to pulmonary fibrosis were assayed in SAHA-treated human peripheral blood mononuclear cells (PBMC) and its subpopulations.SAHA abrogated TGF-β1 effects on all the fibroblast lines by preventing their transdifferentiation into α-SMA positive myofibroblasts and increased collagen deposition without inducing apoptosis. However, MMP1 activity and TIMP1 production was modulated without a clear fibrolytic effect. SAHA also inhibited serum-induced proliferation of the fibroblast lines and caused hyperacetylation of α-tubulin and histone. Cytokine secretion was inhibited from PBMC and lymphocytes at nonapoptotic concentrations. Taken together, these data demonstrate combined antifibrotic and anti-inflammatory properties of SAHA, suggesting its therapeutic potential for pulmonary fibrosis.